Preparation and characterization of new glassy system As2P2S8-Ga2S3 - Santagneli, Silvia H. [UNESP]; Schneider, Jose; Skripachev, Igor [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Amer Chemical Soc, 2008)
Glasses having the composition (100 - x)As2P2S8-xGa(2)S(3) with x ranging from 0 to 50% were investigated to determine the compositional effect on properties and local structure. The glass transition temperature (T-g) and the stability parameter against crystallization (T-x - T-g) increased with the addition of Ga2S3. The structure of these glasses was probed by Raman scattering, Fourier transform infrared (FT-IR) and P-31 nuclear magnetic resonance. on the basis of the observed vibrations and the strength of the P-31-P-31 homonuclear magnetic dipolar coupling, two scenarios can be proposed for the structural evolution induced by the addition of Ga2S3. For x <= 20% we may have the formation of GaS4E- groups (E = nonbonding electron), and for x >= 30% we have depolymerization of the As2P2S8 units and the formation of a network of GaPS4 units with each PS4/2 unit (Q(4)) species carrying a single positive formal charge.